ANALISA PENGARUH BRAND IMAGE DAN CORPORATE BRANDING TERHADAP CONSUMER CHOICE PADA UNIVERSITAS KRISTEN MARANATHA: BRAND EQUITY SEBAGAI VARIABEL MEDIASI ( STUDI PADA SISWA SISWI SMA KRISTEN KOTA BANDUNG) - Allen Kristiawan; Kezia Kurniawaty; Rully Arlan, Tjahyadi; Steven Febriano (FEB Universitas Sam Ratulangi Manado, 2022)
ABSTRACT. Brand Equity is an important factor in marketing development that affects marketing factors such as Consumers Choice. The purpose of this study is to investigate the role of Brand Image and Corporate Branding factors in Brand Equity and their impact when students make choices. This study adopted research variables and instruments from the journal